Family Support, Clinical Profiles, and Psychiatric Comorbidities among Adult Ambulatory HIV/AIDS Patients In A Tertiary are Centre: A Cross-sectional Study - AbdulRauf S. Ibraheem; Louis O. Odeigah; Ibrahim S. Kuranga; Rasaki K. Omowumi; Adisulahi A. Maiyegun; Abayomi O. Ayodapo (Nigerian Frontline Medicine Journal)
Background: People living with Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS), [PLWHA], experience more common psychiatric disorders (CPDs) than the general population, and family support has been reported to influence these disorders. Therefore, this study aimed to determine the relationship between family support, respondents' clinical profiles, and CPDs among PLWHA attending highly active antiretroviral therapy clinics of the University of Ilorin Teaching Hospital Ilorin, Kwara State.